Global shipbuilding activities in the modern maritime market environment - Hess, Mirano (Array, 2020)
The international trade, in the long run being influenced primarily by global economy, is hardly imaginable without maritime transport of goods. The investors in the shipping market, i.e. shipowners, foresee the key return of their capital investments through collection of the freight payments. Consequently, the position and ultimately survival of the owners is intensely influenced with the freight rate cycles, which in turn depend on demand and supply of ships. As historically proved, the higher the freight rates, the more orders for new ships are secured by shipyards. Most of the factors that impact shipowners’ decisions, especially those related to placing the orders, thus extend their influence towards shipyards’ operations and earnings. Competition among shipyards to ever attract more shipowners and secure more new orders or higher value orders, results in expanding their facilities, shortening delivery dates, making their ships’ design more appealing, lowering prices, etc. Observing fluctuations of the market and understanding impact factors on the freight rates’ segment and on shipbuilding segment therefore, is a crucial occupation accompanying executive decision making process for both, shipbuilders and shipowners. Recent state of the global shipbuilding industry is presented in this paper, based on the most recently available data on shipping market and on the global shipbuilding activities. Near-future outlook is given through analysis of the current market developments and industry potentials as well as with respect to the rivalry among competitors. Besides, clarification of market present state’s impact factors is herein given and significant conclusions for their current development and future perspectives are addressed, considering available information.